Rancang Bangun Trainer Kit Pengujian Generator Sinkron AC Dilab. Konversi Energi Politeknik Negeri Manado - Takasihaeng, Daniel William Edward; Mantiri, David Ivanovich Shallom; Pongoh, Deitje Sofie; Doringin, Fanny Jouke; Patabo, Muchdar Daeng; Julianus Gesuri Daud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Synchronous generators are one of the most widely used electrical machines in power systems, especially in power plants. This abstract is based on the background that there are no practical tools specifically used for testing synchronous generators in laboratories, requiring supporting facilities in the form of practical media that can directly support theory and application. The objective of this final project is to design and build a Synchronous Generator Testing Trainer Kit that can be used to perform basic tests such as voltage, current, and frequency using a systematic method that is easy for users to operate. The results of the design show that the trainer kit functions well as a learning medium, as demonstrated by the synchronous generator's stable operation, clearly measurable electrical parameters, and a safe and easy-to-understand testing system, thereby supporting the practical process and understanding of the working concepts of synchronous generators. Based on the results of testing and use of the tool, it can be concluded that the designed synchronous generator testing trainer kit is capable of being a solution to the limitations of practical tools in the laboratory, as well as increasing students' understanding of the working principles and testing of synchronous generators in a practical and applicable manner.